The Cold War in the Middle East : regional conflict and the superpowers, 1967-73 - Ashton, Nigel John (Cold War history series (London, England), 2007)
This edited volume re-assesses the relationship between the United States, the Soviet Union and key regional players in waging and halting conflict in the Middle East between 1967 and 1973. These were pivotal years in the Arab-Israeli conflict, with the effects still very much in evidence today. In addition to addressing established debates, the book opens up new areas of controversy, in particular concerning the inter-war years and the so-called 'War of Attrition', and underlines the risks both Moscow and Washington were prepared to run in supporting their regional clients. The enga.